Rancang Bangun Modul Praktikum Programmable Logic Controller Berbasis Outseal PLC - Langit, Sekar; Rahardjo, Pratolo; Nugraha, I Putu Elba Duta (Majalah Ilmiah Teknologi Elektro, 2024)
In this research, the design of PLC trainer tools and its accessories was carried out to support the making of practicum modules for Programmable Logic Controller + Lab courses by utilizing the Outseal PLC Mega V3 Standard PP board. There are three experimental designs for the practicum module of the Programmable Logic Controller + Lab course, such as running light, water level control, and application of oil to the machine. In general, the design of this practicum module is divided into 3 stages, including system design, hardware design, and software design. Keyword – PLC Trainer; Practicum; Outseal PLC Mega V3 Standard